Usage of Reference Management Software at the University of Torino - Enrico Francese (JLIS.it, 2013)
The present research, originally a master thesis, aims to investigate the popularity and usage of Reference Management Softwares among researchers and scholars of the University of Torino, Italy, and the role that university libraries can assume about the subject. This study, based upon a qualitative approach, is a descriptive survey composed of an online questionnaire and direct interviews addressed to the population of professors and researchers of the STM areas at the University of Torino. A qualitative analysis was made across the 187 responses from the questionnaire and the 13 interviews performed. 7 key concepts were outlined and discussed. The knowledge of Reference Manage Softwares is high among the respondents, but their adoption is not. EndNote is the most known and used software, while other alternatives are more scarcely considered. Scholars, hindered by time issues, rely on old habits and are very unlikely to discover new ways to manage the literature they need. Virtual collaboration is absent from the common research practice.The research gives light on the users' behaviour in a large Italian university, confirming the results provided by the literature. Librarians should assist scholars by providing informations and support about the proper tools to improve the research process.